2023
DOI: 10.1101/2023.06.01.543278
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure and activation of the human autophagy-initiating ULK1C:PI3KC3-C1 supercomplex

Abstract: The unc-51-like kinase protein kinase complex (ULK1C) and the class III phosphatidylinositol (PI) 3-kinase complex I (PI3KC3-C1) are the most upstream and central players in the initiation of macroautophagy. We found a direct physical interaction between the two complexes. The cryo-EM structures of the human ULK1C core and PI3KC3-C1 were determined at amino acid residue-level resolution, and used to interpret a moderate resolution structure of the ULK1C:PI3KC3-C1 supercomplex. The two complexes coassemble thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…96 A, revealing the overall structure of the human PI-3 kinase complex (Fig. 4D) [106,118,119]. These studies unveiled the intricate architecture of this large complex (Fig.…”
Section: The Ulk Complexmentioning
confidence: 75%
See 2 more Smart Citations
“…96 A, revealing the overall structure of the human PI-3 kinase complex (Fig. 4D) [106,118,119]. These studies unveiled the intricate architecture of this large complex (Fig.…”
Section: The Ulk Complexmentioning
confidence: 75%
“…Additionally, negative stain EM and biochemical data indicated that ULK1, ATG13, and FIP200 form a 1 : 1 : 2 complex, with the detailed structure revealed later using cryo-EM assisted with AlphaFold2 (Fig. 3J) [106].…”
Section: The Ulk Complexmentioning
confidence: 84%
See 1 more Smart Citation
“…BECN1 is a key structural component of the class III phosphatidylinositol 3-kinase (PI3Kc3) complexes that are critical for autophagosome nucleation. , BECN1 is a conformationally flexible protein conserved in all eukaryotes that contains at least four domains: an N-terminal intrinsically disordered region (IDR), , a flexible helical domain (FHD), , a coiled-coil domain (CCD), , and a β–α repeated, autophagy-specific domain (BARAD). , The residues comprising these domains in human BECN1 are IDR, residues 1–140, FHD, residues 141–171, CCD, residues 175–265, and BARAD, residues 265–450 . The BARAD bears an aromatic finger comprising residues F359, F360, and W361 that enables BECN1 to interact with membranes. , The BECN1 IDR includes a BH3D, comprising residues 105–130, classifying it as a BH3-only protein .…”
Section: Introductionmentioning
confidence: 99%